PENGARUH CUSTOMER EXPERIENCE DAN CUSTOMER VALUE TERHADAP CUSTOMER LOYALTY INDIHOME (Pada Pelanggan Indihome Area Gegerkalong) - Jumawar, Erwan; Nurmartian, Erika (Program Studi Manajemen, 2021)
This study aims to determine whether customer experience and customer value have an influence on customer loyalty in the Indihome area of ​​Gegerkalong, Bandung, with a sample using Random Sampling with the Slovin formula so that a sample of 73 respondents is obtained and data collection techniques by distributing questionnaires and descriptive analysis approaches that describe the experience customers and customer value to customer loyalty. With quantitative methods and measurement scales using a Likert scale in the form of ordinal data and transformed into interval data with the Successive Interval (MSI) Method which will later be tested for validity, reliability, normality and multiple regression model equations to answer this research. Based on the results of this research test, it shows that the variables Customer Experience (Customer Experience) and Customer Value (Customer Value) have a positive and significant effect on Customer Loyalty (Customer Loyalty) Indihome STO Gegerkalong area and able to explain significantly by 85.4%